The effect of auditory and sensory stimuli – from contemporary music subcultures – on the functional state of young athletes - Marchik, L.A.; Shurekov, V.V.; Abubekyarov, I.A. (Theory and Practice of Physical Culture, 2026)
This article examines the impact of contemporary music genres (rap, electronic music, rock) on the cardiorespiratory system, physical fitness levels and situational anxiety among student athletes aged 18–20. The functional state and mental health of young people are found to be most vulnerable to the negative effects of rock music compared to electronic music and rap.